A novel thermophotovoltaic optical cavity for improved irradiance uniformity and system performance. (15th March 2020) - Zhang, Chao; Tang, Liangliang; Liu, Yan; Liu, Zhuming; Liu, Wei; Qiu, Kuanrong
Abstract: It has been demonstrated that a single thermophotovoltaic (TPV) cell can produce a high-output power density. In practical applications, many such cells are arrayed to obtain a high level of output. However, the irradiance on the surface of each cell of an array may be different. This nonuniformity causes mismatch loss in the array and reduces the reliability of the cells. To address these problems, a novel TPV optical cavity with reflectors was proposed to improve the irradiance uniformity of the cell array. A model TPV system using the proposed cavity was built and evaluated for comparison with traditional systems. TracePro and MATLAB software were used to examine the irradiance uniformity of cell arrays and the electrical performance of TPV systems that incorporate these arrays. Besides system efficiency η system and maximum output power P max, several critical parameters degree of uniformity N, network efficiency η net, and average cell electric power density W ave, were used to evaluate the performance of the TPV systems. The results indicate that the proposed cavity improved the irradiance uniformity of the TPV cell array, thereby reducing mismatch loss and enhancing system performance, and it did so with a reduced number of cells. Highlights: Nonuniform irradiance causes mismatch loss in cell arrays. A novel TPV optical cavity with reflectors was proposed. Irradiance uniformity of TPV cells and TPV system performance were improved.